miR-23a/b clusters are not essential for the pathogenesis of osteoarthritis in mouse aging and post-traumatic models - Fujiwara, Yusuke; Ding, Chenyang; Sanada, Yohei; Yimiti, Dilimulati; Ishikawa, Masakazu; Nakasa, Tomoyuki; Kamei, Naosuke; Imaizumi, Kazunori; Lotz, Martin K.; Akimoto, Takayuki; Miyaki, Shigeru; Adachi, Nobuo (Frontiers in Cell and Developmental Biology, 2023)
Osteoarthritis (OA), the most prevalent aging-related joint disease, is characterized by insufficient extracellular matrix synthesis and articular cartilage degradation and is caused by various risk factors including aging and traumatic injury. Most microRNAs (miRNAs) have been associated with pathogenesis of osteoarthritis (OA) using in vitro models. However, the role of many miRNAs in skeletal development and OA pathogenesis is uncharacterized in vivo using genetically modified mice. Here, we focused on miR-23–27–24 clusters. There are two paralogous miR-23–27–24 clusters: miR-23a-27a-24–2 (miR-23a cluster) and miR-23b-27b-24–1 (miR-23b cluster). Each miR-23a/b, miR-24, and miR-27a/b is thought to function coordinately and complementary to each other, and the role of each miR-23a/b, miR-24, and miR-27a/b in OA pathogenesis is still controversial. MiR-23a/b clusters are highly expressed in chondrocytes and the present study examined their role in OA. We analyzed miRNA expression in chondrocytes and investigated cartilage-specific miR-23a/b clusters knockout (Col2a1-Cre; miR-23a/bflox/flox: Cart-miR-23clus KO) mice and global miR-23a/b clusters knockout (CAG-Cre; miR-23a/bflox/flox: Glob-miR-23clus KO) mice. Knees of Cart- and Glob-miR-23a/b clusters KO mice were evaluated by histological grading systems for knee joint tissues using aging model (12 and/or 18 month-old) and surgically-induced OA model. miR-23a/b clusters were among the most highly expressed miRNAs in chondrocytes. Skeletal development of Cart- and Glob-miR-23clus KO mice was grossly normal although Glob-miR-23clus KO had reduced body weight, adipose tissue and bone density. In the aging model and surgically-induced OA model, Cart- and Glob-miR-23clus KO mice exhibited mild OA-like changes such as proteoglycan loss and cartilage fibrillation. However, the histological scores were not significantly different in terms of the severity of OA in Cart- and Glob-miR-23clus KO mice compared with control mice. Together, miR-23a/b clusters, composed of miR-23a/b, miR-24, miR-27a/b do not significantly contribute to OA pathogenesis.